A geospatial analysis of ecosystem engineer activity and its use during species reintroduction - Andrew P. Stringer; Duncan Blake; David R. Genney; Martin J. Gaywood (European Journal of Wildlife Research, 2018)

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Spatial analysis of ectomycorrhizal fungi reveals that root tip communities are structured by competitive interactions - Brian J. Pickles; David R. Genney; Ian C. Anderson; Ian J. Alexander (Molecular Ecology, 2012)
Microbial ecology has made large advances over the last decade, mostly because of improvements in molecular analysis techniques that have enabled the detection and identification of progressively larger numbers of microbial species. However, determining the ecological patterns and processes taking place in communities of microbes remains a significant challenge. Are communities randomly assembled through dispersal and priority effects, or do species interact with each other leading to positive and negative associations? For mycorrhizal fungi, evidence is accumulating that stochastic and competitive interactions between species may both have a role in shaping community structure. Could the methodological approach, which is often incidence based, impact the outcomes detected? Here, we applied an incidence‐based T erminal R estriction F ragment L ength P olymorphism ( T ‐ RFLP ) database approach to examine species diversity and ecological interactions within a community of ectomycorrhizal ( ECM ) fungi. Co‐occurrence analysis revealed that the ECM community colonizing root tips was strongly structured by competitive interactions, or ecological processes generating a similar spatial pattern, rather than neutral processes. Analysis of β‐diversity indicated that community structure was significantly more similar (spatially autocorrelated) at distances equal to or ECM fungi displayed significant competitive interactions with at least one other species, showing that the incidence‐based approach was capable of detecting this sort of ecological information.